The Relationship Between the Healthy Lifestyle Behaviors of Elderly Individuals and the Perceived Social Support - Polat, Ülkü; Kahraman, Burcu Bayrak (Fırat University, 2013)
Objective: Social support may play an important role in gaining and maintaining healthy lifestyle behaviors of elderly individuals. The aim of the study was to determine the relationship between the healthy lifestyle behaviors of elderly individuals and the perceived social support. Material and Method: A total of 93 elderly individuals who had been coming to the Emek 75. Yıl Elderly Solidarity Center were included in this descriptive study. A questionnaire including the descriptive characteristics of the elderly individuals, the healthy lifestyle behaviors scale (HLBS), and the multi-dimensional perceived social support scale(MPSSS) of were used to gather data. Results: We found a significant relationship between mean score of special person subgroup of MPSSS and mean score of coping with stress subg-roup of HLBS (r=0.207, p

Amaç: Yaşlı bireylerin sağlıklı yaşam biçimi davranışları kazanması ve devam ettirmelerinde sosyal desteğin önemli bir rolü olabilir. Bu çalışmanın amacı “Yaşlı Bireylerin Sağlıklı Yaşam Biçimi Davranışları ve Algılanan Sosyal Destek Arasındaki İlişki”nin belirlenmesidir. Gereç ve Yöntem: Tanımlayıcı tipte olan çalışmaya Emek 75. Yıl Yaşlı Dayanışma Merkezine gelen 93 yaşlı birey alınmıştır. Veri toplama formu olarak; yaşlı bireyin tanıtıcı özelliklerini içeren anket formu, sağlıklı yaşam biçimi davranışları ölçeği (SYBDÖ), çok boyutlu algılanan sosyal destek ölçeği (ÇBASDÖ) kullanılmıştır. Bulgular: Yaşlı bireylerin ÇBASDÖ'nin özel insan alt grubu ile SYBDÖ'nin stresle baş etme alt grubunun puan ortalamaları arasında pozitif yönde anlamlı bir ilişki bulunmuştur(r=0.207). Yalnızca eşi ya da çocuğu ve eşi ile birlikte yaşayanların tüm sosyal destek ölçeği alt grupları ve evli olanların ise özel insan alt grubu puan ortalamasının daha yüksek olduğu belirlenmiştir (p
Yaşlı Bireylerin Sağlıklı Yaşam Biçimi Davranışları ve Algılanan Sosyal Destek Arasındaki İlişki